Therapeutic Public Service Values at the Referal Hospital of East Nusa Tenggara Province - Kewuan, Nikolaus Nuke; Oedjoe, Mintje Ratoe; Kase, Petrus; Nursalam (Migration Letters, 2024)
The aim of the research is to analyze the influence of: Commitment, Integrity, Transparency, Therapeutic Communication on Competence and Quality of Public Services; Therapeutic-Based Public Service Value Mapping Model in Referral Hospitals of East Nusa Tenggara Province. Type of quantitative research. The instrument uses a questionnaire given to 240 respondents, namely patients/patient families. Statistical test with Structural Equation Model Partial Least Square (SEM PLS). The research results show the influence of: Commitment to the Quality of Public Services with t statistic of 3.780 (p=0.000) and indirectly through Competency with t statistic of 1.277 (p=0.202); Integrity towards the Quality of Public Services with t statistic of 0.817 (p=0.414) and indirectly through Competence with t statistic of 2.571 (p=0.010); Transparency on the Quality of Public Services with t statistic of 0.892 (p=0.372) and indirectly through Competency with t statistic of 2.086 (p=0.037); Therapeutic Communication on the Quality of Public Services with t statistic of 6.661 (p=0.000) and indirectly through Competency with t statistic of 2.327 (p=0.020); Competence in the Quality of Public Services with t statistic of 2.664 (p=0.008) and the Promotion of the Therapeutic Public Service Values Model "Korke Bale" in Public Services at Referral Hospitals in East Nusa Tenggara Province.